2017
DOI: 10.1080/1406099x.2017.1308781
|View full text |Cite
|
Sign up to set email alerts
|

Is the success of an issuer an investor success? Evidence from Polish IPOs

Abstract: This article examines the factors that determine IPO success in raising equity capital, and how this success translates into investor success. The study is based on a sample of IPOs on the Warsaw Stock Exchange from 1998 to 2011. We find that pre-IPO profitability is a strong and positive signal for investors that translates into a higher offer price and therefore determines the success of the issuance. However, companies with high IPO success do not provide investors with better performance after going public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 65 publications
0
10
0
1
Order By: Relevance
“…The success or failure (performance) of an IPO have different meaning for both the issuer and the investor. For issuer, the success of an IPO is measured by the amount of capital raised by them without losing their control over the company (Brycz et al, 2017). From the investor's perspective, the success of an IPO is measured in form of the returns he/she makes by selling these securities in future.…”
Section: Ownership Structure and Market Sentimentmentioning
confidence: 99%
See 1 more Smart Citation
“…The success or failure (performance) of an IPO have different meaning for both the issuer and the investor. For issuer, the success of an IPO is measured by the amount of capital raised by them without losing their control over the company (Brycz et al, 2017). From the investor's perspective, the success of an IPO is measured in form of the returns he/she makes by selling these securities in future.…”
Section: Ownership Structure and Market Sentimentmentioning
confidence: 99%
“…An IPO serves the objective of companies as the sale of new shares provides them with fresh capital. It also presents an opportunity for investors to best allocate their capital (Brycz et al, 2017) for future returns. Investors can realize returns in future upon selling these securities post their allotment and formal listing.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between around-the-IPO profitability was not so evident for long-term abnormal performance measured with BHARs as it was not robust to alternative methods. Brycz et al (2017) found that short-term IPO success is strongly determined by pre-IPO profitability, with no significant results for the long-term buy-and-hold returns. We propose to test the relationship for Polish IPOs using the improved estimation method of long-term performance.…”
Section: Related Literaturementioning
confidence: 90%
“…The first studies mainly focused on the privatization issues (Aussenegg 2000;Jelic and Briston 2003;Lyn and Zychowicz 2003). More recently, long-term underperformance was found with the buy-and-hold approach, according to different benchmarks (Jewartowski and Lizińska 2012;Lizińska and Czapiewski 2016;Brycz et al 2017).…”
Section: Related Literaturementioning
confidence: 99%
“…Długoterminowy underperformance, na który wskazywało wiele badań dla zagranicznych rynków, został również wykazany dla Polski (por. Brycz, Dudycz, Kowalski, 2017;Czapiewski, Lizińska, 2014;Jewartowski, Lizińska 2012;Lizińska, Czapiewski, 2016c).…”
Section: Efekty Związane Z Publikacją Informacji O Spółceunclassified